2010
DOI: 10.1002/micr.20766
|View full text |Cite
|
Sign up to set email alerts
|

Assessing suturing techniques using a virtual reality surgical simulator

Abstract: Advantages of virtual-reality simulators surgical skill assessment and training include more training time, no risk to patient, repeatable difficulty level, reliable feedback, without the resource demands, and ethical issues of animal-based training. We tested this for a key subtask and showed a strong link between skill in the simulator and in reality. Suturing performance was assessed for four groups of participants, including experienced surgeons and naive subjects, on a custom-made virtual-reality simulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
(21 reference statements)
1
18
0
Order By: Relevance
“…1 Various simulation assessment tools have been validated and deemed reliable in measuring residents' technical skills outside the operating room across multiple specialties, including microsurgery. 3,[5][6][7][8][9][10][11][12][13] In addition, various simulation training modules have been validated for improving performance in the operating room with training. [14][15][16][17][18][19][20] Despite these advances in microsurgical education, it is unknown how prevalent simulation is.…”
mentioning
confidence: 99%
“…1 Various simulation assessment tools have been validated and deemed reliable in measuring residents' technical skills outside the operating room across multiple specialties, including microsurgery. 3,[5][6][7][8][9][10][11][12][13] In addition, various simulation training modules have been validated for improving performance in the operating room with training. [14][15][16][17][18][19][20] Despite these advances in microsurgical education, it is unknown how prevalent simulation is.…”
mentioning
confidence: 99%
“…The lack of haptic feedback is another criticism of the virtual reality simulators. Studies on Virtual reality technology when applied to microsurgical training have concluded that it needs to be used in combination with other objective assessment tools until more research is conducted in this field to demonstrate its feasibility as an objective assessment tool in comparison to current more developed tools like the global rating scale …”
Section: Virtual Reality (Vr) Simulatorsmentioning
confidence: 99%
“…Most studies on operator performance have utilized "metrics." [6][7][8][9][10][11][12][13][14][15][16] A useful definition of "metrics" is that they are standards of reference by which performance, efficiency, and progress can be assessed. Individual metric can be used to assess aspects of operator performance.…”
Section: Introductionmentioning
confidence: 99%